“SHARING ECONOMY” THE CASE OF AIRBNB IN NCR: AN HONESTLY SIGNIFICANT DIFFERENCE (HSD) TEST - Mary Vida L. Tumbali, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
As opposed to the traditional market model, which is based on possession, the ‘Sharing Economy’ is based on sharing and utilizing services and products among others. Airbnb founded by Joe Gebbia and Brian Chesky in 2008, is one the best example of the Sharing Economy. The purpose of this paper was to determine and compare the market revenue and occupancy rates of the selected cities in the National Capital Region from 2016-2019. Secondary Data was from AirDNA - a paid service tool intentional for Airbnb researchers. One-way Anova was the statistical test used in this study, followed by an honestly significant difference (HSD) test. This research paper covered seven (7) selected cities in the National Capital Region. These are the City of Manila, Makati, Mandaluyong, Pasay, Parañaque, Pasig, and Quezon City. The results revealed that in the year 2016-2019 Manila appeared to have the highest percentage of occupancy rate, while Makati City gained the highest amount of Market Revenue.